TRAINING ON FOOD PACKAGING FOR MSMEs SENDEN VILLAGE TRENGGALEK BY UNAIR TEAM & PARTNER UNIVERSITIES - Aminah, Nanik Siti; Kristanti, Alfinda Novi; Ramadhan, Rico; Hendradi, Rimuljo; Takaya, Yoshiaki; Khoso, Mir Hasan; Baharin, Siti Nor Atika; Abdjan, Muhammad Ikhlas (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
The International Community Services program (ICS) at Universitas Airlangga, part of the Tri Dharma of the university focusing on community service, aims to enhance human resource capacities within communities. In 2024, the program targeted Senden Village, Kampak sub-District, Trenggalek District, East Java, Indonesia, to assist its MSMEs in overcoming packaging challenges that hinder market interest. Collaborating with domestic and international universities, including Universitas Mayjen Sungkono, SMBBMU University Larkana Pakistan, UiTM Negeri Sembilan Malaysia, UM Malaysia, and Meijo University Japan, the program provided intensive training on innovative and functional packaging techniques. This program was chosen and considered urgent because processed food products produced by local MSMEs are still sold in bulk and packaged haphazardly. Therefore, a touch of hygienic and "eye-catching" packaging technology is needed. Attractive and hygienic packaging technology is expected to increase the selling power of these processed food products. The training included theoretical sessions, focus group discussion (FGD) demonstrations, and the introduction of plastic vacuum sealers to improve product packaging and branding. Food packaging workshop held on July 15, 2024, where participants engaged in hands-on training, group discussions, and label design, resulting in tangible improvements in product marketability. The initiative of this activity is not only to increase the visibility and attractiveness of Senden Village products but also to introduce the natural exotism of the village and local products to the national and international community, encouraging cultural and knowledge exchange. The collaboration of this program strengthens international collaboration and provides invaluable experience for students and lecturers. The successful implementation of this program confirms Airlangga University's commitment to community service and its goal of creating a sustainable positive impact on the village community, which ultimately contributes to the development of better human resources. The training has been carried out very well and each training participant has their own brand with an attractive logo and is hygienically packaged with vacuum technology. All training participants were satisfied with this activity as well as head of village, head of PKK, and all the team involved. They hope that next year's activities can be carried out with other innovations for the progress of Senden village.